Quality control for the diagnosis of helminths in Villa Clara province, Cuba: 2016-2019 - Córdova-Martínez, Rosa Laura (2023)
Helminthic diseases are a major public health problem. Laboratory diagnosis is of vital importance, which must be supported by a quality assurance system. The objective of the study was to carry out an external evaluation of the laboratories that make up the health care network in order to compare the results of the external quality control in the diagnosis of helminths of the governing laboratory, the Provincial Center of Hygiene, Epidemiology and Microbiology, with the participants in Villa Clara province, Cuba. A descriptive and transversal study was carried out, with a discretional sampling of intentional type by criteria. A total of 2,857 stool samples from 36 laboratories were processed from March 2016 to March 2019 by the Willis - Molloyʹs high-density solution method. In 98.6% of the diagnoses there was concordance of results and no concordance in 1% (29), in addition to 7 (0.2%) discrepant and 4 (0.1%) polyparasitized. Of 93 identified helminths, Enterobius vermicularis (Linnaeus, 1758) was present most frequently with 32, Ascaris lumbricoides (Linnaeus, 1758) with 27 and Necator/Ancylostoma with 8, for 82.8%; of the seven discrepant, two were diagnosed as Necator/Ancylostoma (participants)/ were Strongyloides stercoralis (Bavay, 1876) (rector). The participating laboratories were considered to have high quality assurance, because of the almost absolute predominance of concordant samples. The low presence of intestinal helminths in the samples received was confirmed. There are some difficulties in the identification of intestinal helminth eggs and/or larvae.